A study on conflict resolution at Perbadanan Labuan / Md Faizal Azis and Zulyazfie Abd Rasa - Azis, Md Faizal; Abd Rasa, Zulyazfie (2013)
This study was conducted to investigate the differences in choosing the conflict resolutions with regards to demographic characteristics. The sample of 100 respondents from Perbadanan Labuan selected randomly to answer the questionnaire in this research. The results of this study will indicates the factors that affect the employee's style of handling conflicts may help managers to predict the behaviour of their employees in such conflicts.